The brain : big bangs, behaviors, and beliefs - DeSalle, Rob (Yale University Press, 2012)
After several million years of jostling for ecological space, only one survivor from a host of hominid species remains standing: us. Human beings are extraordinary creatures, and it is the unprecedented human brain that makes them so. In this book the authors present a step-by-step account of the evolution of the brain and nervous system. Tapping the very latest findings in evolutionary biology, neuroscience, and molecular biology, the authors explain how the cognitive gulf that separates us from all other living creatures could have occurred. They discuss the development and uniqueness of human consciousness, how human and nonhuman brains work, the roles of different nerve cells, the importance of memory and language in brain functions, and much more. Our brains, they conclude, are the product of a lengthy and supremely untidy history, an evolutionary process of many zigs and zags, that has accidentally resulted in a splendidly eccentric and creative product.